2007
DOI: 10.4319/lo.2007.52.3.1258
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and oxygen isotopic signatures of subsurface nitrate seaward of the Florida Keys reef tract

Abstract: Hydrographic and nutrient structure and the nitrogen and oxygen isotopic compositions (60.14) within the chlorophyll maximum layer to 3.02% (60.07) below the thermocline. These observations suggest an oceanic, deep-water nitrate source below the thermocline, a mix of sources from upwelling and N 2 fixation, and the effects of fractionation associated with uptake by primary producers within the thermocline. The water column nitrate isotopic data support the general hypothesis that primary producers on the Flori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 41 publications
4
30
0
Order By: Relevance
“…Temperatures below approximately 26°C correspond to water masses at or below the thermocline and the concentrations of both nitrate and phosphate increased nearly linearly with decreasing temperature (data shown here, and in Leichter et al 2003Leichter et al , 2007. The data from 30 to 70 m depth show increasing exposure to low temperatures with increasing depth and suggest that the main thermocline was often at approximately 50 to 60 m depth, with frequent incursions into shallower depths.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Temperatures below approximately 26°C correspond to water masses at or below the thermocline and the concentrations of both nitrate and phosphate increased nearly linearly with decreasing temperature (data shown here, and in Leichter et al 2003Leichter et al , 2007. The data from 30 to 70 m depth show increasing exposure to low temperatures with increasing depth and suggest that the main thermocline was often at approximately 50 to 60 m depth, with frequent incursions into shallower depths.…”
Section: Discussionsupporting
confidence: 54%
“…Estimates of the fluxes of inorganic nutrients across the slope of Conch Reef in the Florida Keys suggest increases of more than an order of magnitude during internal wave events relative to non-internal wave periods (Leichter et al 2003). Previous studies have shown that the common benthic macroalga Codium isthmocladum likely uses transiently available nitrate (Leichter et al 2003(Leichter et al , 2007. Further evidence of algal utilization of transient nutrient pulses at this site was provided by Smith et al (2004) who showed increased growth rates and a decreased effect of artificial nutrient additions for the benthic alga Halimeda tuna with increasing depth from 7 to 21 m. A complete nutrient budget for the FLKRT has not been developed, but high frequency upwelling appears to be a significant overall nutrient source for the outer reef slopes (Boyer & Jones 2002, Kruczynski & McManus 2002, Leichter et al 2003.…”
Section: Abstract: Macroalgae · Florida Keys · Coral Reefs · Light ·mentioning
confidence: 99%
“…Introduction of upwelled subthermocline water into reef communities and the possible effects on water quality (Andrews & Gentien 1982, Leichter et al 1996, Leichter et al 2007), biodiversity (Cortés 1997) Genovese 2006) and among the highest so far observed (Sheppard 2009). Given the proximity of the W (LAIW+) and E (LAIW-) sides of the islands (< 200 m), the differences in the physical oceanographic parameters between the 2 island sides are striking.…”
Section: Discussionmentioning
confidence: 99%
“…Both of the heavier isotopes of NO 3 (i.e., 15 N and 18 O) react more slowly in enzyme-mediated reactions, such as NO 3 assimilation and denitrification, resulting in a gradual increase in heavier isotopes of the remaining NO 3 at a specific ratio (e.g., 18 ε: 15 ε = 1 for assimilation by eukaryotic phytoplankton and cyanobacteria; 18 ε : 15 ε = 2 for heterotrophic bacteria [Granger et al, 2004[Granger et al, , 2010; and 18 ε : 15 ε = 0.5 to 1.0 for denitrification [Chen and MacQuarrie, 2005;Granger et al, 2008], where 18 ε and 15 ε [‰] are kinetic isotope effects expressed as the ratio of the reaction rates [k] for the heavy and light isotopes as follows: 18 ε [ 15 ε] = ( 16 k/ 18 k[ 14 k/ 15 k] − 1) × 1000) and various values in each N pool of the natural environment. Therefore, when the values of stable isotopes of each NO 3 source are distinct from those of other sources, the information can be used to trace the contribution of each NO 3 source (Leichter et al, 2007). Also, when NO 3 is taken up by phytoplankton and bacteria following a Rayleigh fractionation model in a closed system, a linear relationship is observed between the log-transformed NO 3 concentration (ln[NO 3 ]) and δ 15 N in NO 3 (Sigman et al, 1999;Teranes and Bernasconi, 2000).…”
Section: Y Umezawa Et Al: Seasonal Shift Of the Nitrate Sources In mentioning
confidence: 99%